Are intra-household allocations policy neutral? Theory and empirical evidence - Pierre-André Chiappori; Murat Iyigun; Jeanne Lafortune; Yoram Weiss (Institute for the Study of Labor (IZA), 2011)
We develop a collective household model with spousal matching in which there exists marital gains to assortative matching and marriage quality for each couple is revealed ex post. Changes in alimony laws are shown to affect existing couples and couples-to-be differently. For existing couples, legislative changes that favor (wo)men benefit them especially if the marriage match quality is low, while, for couples not yet formed, they generate offsetting intra-household transfers and lower intra-marital allocations for the spouses who are the intended beneficiary. We then estimate the effect of granting alimony rights to cohabiting couples in Canada using a triple-difference framework since each province extended these rights in different years and requiring different cohabitation length. We find that obtaining the right to petition for alimony led women to lower their labor force participation. These results, however, do not hold - and, in some cases, are reversed - for newly formed cohabiting couples.
urn:nbn:de:101:1-201104134161
Keywords: J12; J16; J24; 330; intra-household allocations; matching; cohabitation; alimony laws; Familienökonomik; Lebensgemeinschaft; Unterhaltsrecht; Wirkungsanalyse; Ehe; Matching; Kanada